Identificación de tipos de injertos utilizados en el cultivo de Guanábana (Annona muricata L.), en el Ecuador. - Guzmán Nevares, Miguel Angel (2022)
This paper addressed the issue of the types of grafts that are used in the cultivation of Soursop (Annona muricata L.), in Ecuador. Due to the lack of knowledge that exists about what is the type of graft that should be used in soursop, the main objective was to identify the types of graft that are used in soursop plants in Ecuador. A methodology with a qualitative approach and descriptive scope was proposed. For the preparation of this document, information was sought in updated texts, web pages, journals, scientific articles, virtual libraries and all valuable bibliographic material for the development of this research. The graft consists of joining two plants one that will have the roots called (pattern) and the other that will be composed of the buds with the name of (graft), the grafting techniques are widely used and favorable to produce soursop, because these eliminate the juvenile stage of the plant. The results show that the types of graft used in soursop are: lateral barb, splice, simple cleft, yolk. The most effective for soursop is the simple cleft graft since it has higher percentages of effectiveness.